Detoxification of aflatoxin B1 in broiler chickens by a triple-action feed additive. Issue 9 (2nd September 2021) - Guo, Hongwei; Chang, Juan; Wang, Ping; Yin, Qingqiang; Liu, Chaoqi; Li, Silu; Zhu, Qun; Yang, Mingfan; Hu, Xiaofei
ABSTRACT: The aim of this study was to evaluate the detoxification of aflatoxin B1 (AFB1 ) in vitro and in broiler chickens using a triple-action compound mycotoxin detoxifier (CMD). Response surface methodology (RSM) was used to evaluate AFB1 detoxification in artificial gastrointestinal fluid (AGIF) in vitro . The AFB1 -degradation rate was 41.5% ( P < .05) when using a compound probiotic (CP) in which the visible counts of Bacillus subtilis, Lactobacillus casein, Enterococcus faecalis and Candida utilis were 1.0 × 10 5, 1.0 × 10 5, 1.0 × 10 7 and 1.0 × 10 5 CFU/mL, respectively. When CP was combined with 0.1% AFB1 -degrading enzyme to give CPADE, the AFB1 -degradation rate was increased to 55.28% ( P < .05). The AFB1 -removal rate was further increased to above 90% when CPADE was combined with 0.03% montmorillonite to make CMD. In vivo, a total of 150 one-day-old Ross broilers were allotted to 3 groups, 5 replications for each group, 10 broilers in each replication. Group A: basal diet, Group B: basal diet with 40 μg/kg AFB1, Group C: basal diet with 40 μg/kg AFB1 plus CMD. The feeding experiment period was 21 d. The results showed that broiler growth was increased, and AFB1 residues in serum, excreta and liver were decreased by CMD addition in broiler diet ( P < .05). In conclusion, CMD was able to remove AFB1 efficiently in vitro and to increase broiler production performance and reduce AFB1 residues in the chickens.